The impact of pandemics on education—“a nice monster of COVID-19”—Mini review - Mǎrginean, Cristina Oana; Meliţ, Lorena Elena; Vǎsieşiu, Anca Meda; Anzanello, Andrea; Antão, Celeste; Bredelyte, Aelita; Tsakalidis, Christos; Lupescu, Radu; Azamfirei, Leonard (Frontiers in Education, 2024)
The aim of this review was to underline the best teaching model for training specialist nurses.Thus, the healthcare systems should work along with national agencies for designing and implementing complex curricula for training specialists in providing healthcare such as specialist nurses or advanced practice nurses involved in the decision-making process. The educational process for these nurses should be based on an international standard involving digital education techniques such as e-learning platform, interactive approaches of the course content, as well as an interactive teaching system based on figures, graphics or videos. Moreover, virtual reality based-medical models should also represent an important aspect of the training program in order to provide the future students with the opportunity to deal with real-life medical situations in advance.These techniques will form the basis of the specialist nurses' up-skilling process resulting in crucial life savior medical competences.The trainers should embrace their new roles in the educational process being aware that the nowadays teaching concept is no longer based on a governance approach, but they should rather mediate, guide and organize the educational process becoming shadow partners of their students in achieving the desired skills.The assessment of the students should also comply to the digitalization process by including novel evaluation techniques such as quizzes, individual and team assignments, objective structured clinical examination in order to objectively mirror the student's progress during the training program.Therefore, this review synthetized current insights in learning and training techniques that should be implemented for addressing the needs of innovation in medical education.